Tropical cyclone losses in the USA and the impact of climate change: a trend analysis based on a new dataset - Silvio Schmidt; Claudia Kemfert; Peter Höppe (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Economic losses caused by tropical cyclones have increased dramatically. It can be assumed that most losses are due to increased prosperity and a greater tendency for people to settle in exposed areas, but also that the growing incidence of severe cyclones is due to climate change. This paper aims to isolate the socio-economic effects and ascertain the potential impact of climate change on this trend. Storm losses for the period 1950-2005 have been adjusted to 2005 socio-economic values so that any remaining trend cannot be ascribed to socio-economic developments. In the period 1971-2005, losses excluding socio-economic effects show an annual increase of 4% per annum.
Keywords: Q54; Q50; Q51; 330; Climate change; tropical cyclones; loss trends; Sturm; Soziale Kosten; Klimaveränderung; Sozialer Wandel; USA